Preliminary studies into the secondary transfer of undeveloped latent fingermarks between surfaces - Jabbal, R.; Boseley, R.; Lewis, Simon (International Association for Identification, 2018)
This study investigates the conditions under which undeveloped fingermarks will transfer between surfaces that have come into contact. Latent fingermarks were deposited on a glass surface, which was brought into contact with paper surfaces for varying periods of time and pressure. Subsequently, the paper was treated with a variety of development procedures including 1, 2-indanedione-zinc, ninhydrin, Oil red 0, aqueous Nile blue, and SMD II. 1, 2-Indanedione-zinc was successful at detecting transferred fingermarks, with good contrast and ridge definition, observed when fresh fingermarks were transferred by contact with the secondary surface for a minimum of 24 hours under a 5.00 kg pressure. The high degree of clarity and contrast of the developed transferred fingermark made it difficult to differentiate as a secondary mark. Transferred marks can only be recognized as a mirror image when compared to a mark directly deposited from an individual.